The oncolytic virus Delta-24-RGD elicits an antitumor effect in pediatric glioma and DIPG mouse models - Naiara Martínez-Vélez (Nature Portfolio, 2019)
The oncolytic virus Delta-24-RGD is in clinical trial for adult glioma. Here, the authors show that this virus elicits an immune response in mouse models of pediatric high-grade glioma and diffuse pontine intrinsic glioma, resulting in improved survival.